Lie symmetry analysis, exact solutions and conservation laws for the time fractional Caudrey-Dodd-Gibbon-Sawada-Kotera equation - Baleanu, Dumitru; İnç, Mustafa; Yusuf, Abdullahi; Aliyu, Aliyu Isa (Elsevier, 2018)
In this work, we investigate the Lie symmetry analysis, exact solutions and conservation laws (Cls) to the time fractional Caudrey-Dodd-Gibbon-Sawada-Kotera (CDGDK) equation with Riemann-Liouville (RL) derivative. The time fractional CDGDK is reduced to nonlinear ordinary differential equation (ODE) of fractional order. New exact traveling wave solutions for the time fractional CDGDK are obtained by fractional sub-equation method. In the reduced equation, the derivative is in Erdelyi-Kober (EK) sense. Ibragimov's nonlocal conservation method is applied to construct Cls for time fractional CDGDK. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Time fractional CDGDK; Lie symmetry; RL fractional derivative; exact solutions; Cls